Adaptation of the Tele-Harm Reduction intervention to promote initiation and retention in buprenorphine treatment among people who inject drugs: a retrospective cohort study. (31st December 2023) - Suarez, Edward; Bartholomew, Tyler S.; Plesons, Marina; Ciraldo, Katrina; Ostrer, Lily; Serota, David P.; Chueng, Teresa A.; Frederick, Morgan; Onugha, Jason; Tookes, Hansel E.
Abstract: Background: At the start of the pandemic, relaxation of buprenorphine prescribing regulations created an opportunity to create new models of medications for opioid use disorder (MOUD) delivery and care. To expand and improve access to MOUD, we adapted and implemented the Tele-Harm Reduction (THR) intervention; a multicomponent, telehealth-based and peer-driven intervention to promote HIV viral suppression among people who inject drugs (PWID) accessing a syringe services program (SSP). This study examined buprenorphine initiation and retention among PWID with opioid use disorder who received the adapted THR intervention at the IDEA Miami SSP. Methods: A retrospective chart review of participants who received the THR intervention for MOUD was performed to examine the impact of telehealth on buprenorphine retention. Our primary outcome was three-month retention, defined as three consecutive months of buprenorphine dispensed from the pharmacy. Results: A total of 109 participants received the adapted THR intervention. Three-month retention rate on buprenorphine was 58.7%. Seeing a provider via telehealth at baseline or any follow up visit (aOR = 7.53, 95% CI: [2.36, 23.98]) and participants who had received an escalating dose of buprenorphine after baseline visit (aOR = 8.09, 95% CI: [1.83, 35.87]) had a higher adjusted odds of retention at three months. Participants who self-reported or tested positive for a stimulant (methamphetamine, amphetamine, or cocaine) at baseline had a lower adjusted odds of retention on buprenorphine at three months (aOR = 0.29, 95% CI: [0.09, 0.93]). Conclusions: Harm reduction settings can adapt dynamically to the needs of PWID in provision of critical lifesaving buprenorphine in a truly destigmatising approach. Our pilot suggests that an SSP may be an acceptable and feasible venue for delivery of THR to increase uptake of buprenorphine by PWID and promote retention in care. KEY MESSAGES: The Tele-Harm Reduction intervention can be adapted for initiating and retaining people who inject drugs with opioid use disorder on buprenorphine within a syringe services program setting Using telehealth was associated with increased three-month buprenorphine retention Baseline stimulant use was negatively associated with three-month buprenorphine retention